The stair-step approach in treatment of anovulatory PCOS patients - Eran Horowitz; Ariel Weissman (SAGE Publishing, 2020)
Clomiphene citrate (CC) is a widely accepted first-line treatment for anovulatory patients with polycystic ovarian syndrome (PCOS). The current practice is to prescribe CC with gradual dose increments until ovulation is achieved. Typically, progesterone withdrawal bleeding is induced between each dose increment and before the commencement of gonadotropin therapy in CC-resistant patients. It has been recently suggested that dose increments of CC can be administered once failure to induce ovulation at a certain dose has been documented, without induction of progesterone withdrawal bleeding, and this approach has been nicknamed the clomiphene-citrate stair-step (CC-SS) protocol. The same principle has been found feasible before introducing gonadotropin therapy in CC-resistant PCOS patients. Our objective was to review the world literature on the CC-SS protocol and to summarize our own experience with extending the CC-SS approach to initiation of gonadotropin therapy. Studies on CC-SS protocol ( n  = 4) have found that this approach leads to a significant reduction of the time to ovulation and to an increased ovulation rate. In our own retrospective case series, 18 CC-resistant PCOS patients initiated gonadotropin stimulation without induction of progesterone withdrawal bleeding, using the chronic low-dose regimen. The time to ovulation in the study group was 54.2 ± 6.2 days, while the estimated time to ovulation calculated according to the traditional approach was approximately 110 days. The clinical pregnancy rate was 44% (8/18), and all pregnancies were singletons. One patient miscarried; hence, the live birth rate was 38.9% (7/18). In summary, the CC-SS approach and its extension to the initiation of gonadotropin therapy results in considerable reduction of the time to ovulation, and favorable ovulation rates and reproductive outcome. Large-scale confirmation of these findings by properly designed randomized controlled trials may lead to a change of practice in the treatment of anovulatory infertility in PCOS patients, allowing simplification of treatment and a shorter time to ovulation and pregnancy.